2006
DOI: 10.2460/ajvr.67.9.1519
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin concentrations in synovial fluid obtained from the tarsocrural joints of horses after implantation of gentamicin-impregnated collagen sponges

Abstract: Implantation of a gentamicin-impregnated collagen sponge in the tarsocrural joint of horses resulted in rapid release of gentamicin, with peak concentrations > 20 times the minimum inhibitory concentration reported for common pathogens that infect horses. A rapid decrease in synovial fluid gentamicin concentrations was detected. The purified bovine type I collagen sponges did not elicit substantial inflammation in the synovial membrane or cause mechanical trauma to the articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
3
19
2
Order By: Relevance
“…This is in contrast to studies 8,13 performed with gentamicin in horses. Blood, synovial fluid of control joints, and specimens of organs had negative results.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This is in contrast to studies 8,13 performed with gentamicin in horses. Blood, synovial fluid of control joints, and specimens of organs had negative results.…”
Section: Discussioncontrasting
confidence: 80%
“…4,5,[7][8][9][10][11] Additionally, some of these drugs have been tested in controlled-release formulations to decrease the number of arthrocentesis procedures needed for treatment. 4,12,13 However, some of these drugs can induce tissue irritation, 8,14,15 and their antimicrobial spectrum does not always match the microorganisms isolated from cattle. 4,16 Doxycycline is a semisynthetic antimicrobial of the tetracycline group.…”
mentioning
confidence: 99%
“…Currently, local antimicrobials can be delivered by serial intra‐articular injections, serial regional limb perfusions, continuous infusion pumps, or intra‐articular placement of antimicrobial impregnated implants 1,5,8–12 . Although effective, serial intra‐articular injections and regional limb perfusions can be technically challenging in a limb with secondary cellulitus, 1 and unfeasible in the proximal aspect of the limb of horses where tourniquet placement is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, Plaster of Paris beads have not been assessed in vivo in horses so the erosive effects on cartilage and synovium are unknown. A pharmacokinetic study on the use of gentamicin impregnated collagen sponges concluded that they do not offer any direct advantage over direct intra‐articular injection of the same drug 12 . Therefore a need exists for the development of a new absorbable implant that ideally would be made from a bioabsorbable matrix and would release antimicrobial concentrations within the therapeutic range for an extended period.…”
Section: Introductionmentioning
confidence: 99%
“…Many bioabsorbable carriers have been investigated including protein materials, bone graft materials and substitutes, and synthetic polymers. Protein materials including collagen sponge, 11,12 fibrinogen, 13 gelatin, 14,15 albumin, ferric‐hyaluronate, 16 R‐gel ™ , 17 and autologous blood clot have all been described but suffer from very short‐term antibiotic release over hours to days 9 . Bone graft materials and substitutes for antibiotic delivery and release include calcium sulfate (plaster of Paris), 18,19 calcium sulfate wrapped in porcine small intestinal submucosa, 20 calcium phosphate cement, 10,21,22 hydroxyapatite cement, 18,23 calcium sulfate and hydroxyapatite combination, 24 bioactive glass, and cancellous bone graft 9 .…”
mentioning
confidence: 99%